Influence of exchange cations on the catalytic conversion of limonene over Serra de Dentro (SD) and SAz-1 clays: correlations between acidity and catalytic activity/selectivity - Catrinescu, C. (2021)
A bentonite collected at Serra de Dentro (SD), Porto Santo Island, Portugal, and the source clay SAz-1 (Cheto, Arizona) were ion-exchanged with different cations (Al3+, Ni2+, Cr3+ and Na+ ). Variable temperature diffuse reflectance infrared Fourier transform spectroscopy (VT-DRIFTS) of pyridine treated samples, thermal desorption of cyclohexylamine and real time mass spectrometry of the evolved gases were used to evaluate the acidic properties of the prepared catalysts. The catalytic activity of these ion-exchanged clays was tested in the acid-catalysed conversion of limonene at 150 8C, to yield isomerization products (terpinolene, a-terpinene, g-terpinene and isoterpinolene), disproportionation products ( p cymene and p-menthenes) and high molecular-weight compounds. The possibility of increasing the selectivity toward p-cymene, over a catalyst with substantial Lewis acid character, was particularly envisaged. Catalysts derived from SD were significantly more active than their SAz-1 counterparts. This was mainly attributed to the greater inherent acidity, to the higher structural iron content (providing dehydrogenation activity) and to the higher nitrogen surface area of the starting SD clays. Within the Mn+ -SD series, the order of activity decreased as Ni2+ > Al3+ > Cr3+ > Na+ . A direct comparison between Al3+-SD (with maximized Bro¨nsted acidity) and Ni2+-SD (with predominant Lewis acid character) provided no support for enhanced p-cymene production over Lewis acid sites.